2009
DOI: 10.1080/02656730902873616
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiological and pathohistological response to neoadjuvant chemotherapy combined with regional hyperthermia (RHT) and study of response dependence on the applied thermal parameters in patients with soft tissue sarcomas (STS)

Abstract: SD or PR in radiological response assessment does not correlate with the pathohistological response after neoadjuvant thermochemotherapy. RECIST, WHO and volumetric criteria for response evaluation in STS are in substantial agreement. For irregularly shaped lesions, volumetric criteria seem to be more appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
1
11
0
2
Order By: Relevance
“…Furthermore, changes in radiographic tumor size, as measured by RECIST, also seem to be a poor surrogate of disease control and oncologic outcome 18,20. Our findings are consistent with both of these conclusions and reaffirm that novel imaging end points for STS are needed 17,21…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, changes in radiographic tumor size, as measured by RECIST, also seem to be a poor surrogate of disease control and oncologic outcome 18,20. Our findings are consistent with both of these conclusions and reaffirm that novel imaging end points for STS are needed 17,21…”
Section: Discussionsupporting
confidence: 85%
“…chemotherapy)-induced changes of sarcomas measured clinical response with all 3 possible radiological anatomic response criteria from unidimensional to tridimensional, which is similar to this study. In general, the study by Stahl et al 21 failed to document a correlation between radiology and pathology, especially for radiologic partial responders and cases with stable disease. The authors concluded that anatomic response criteria may be able to detect only progressive disease stages.…”
Section: Discussionmentioning
confidence: 94%
“…[16][17][18] Similar to our results, others observed that cystic degeneration as part of posttherapeutic tumor changes are often associated with tumor size increases in pathological responders after RT. 19,20 A study by Stahl et al 21 of the hyperthermia (? chemotherapy)-induced changes of sarcomas measured clinical response with all 3 possible radiological anatomic response criteria from unidimensional to tridimensional, which is similar to this study.…”
Section: Discussionmentioning
confidence: 99%
“…However other means of response evaluation, especially radiological re-staging during or shortly after neoadjuvant treatment, are even less reliable. Re-Staging does neither seem to correlate with histopathological response nor with outcome after preoperative HCT or radiotherapy [47][48][49]. Therefore histological evaluation can still be regarded as the gold standard for response evaluation.…”
Section: Discussionmentioning
confidence: 97%